Murder by the book : the crime that shocked Dickens's London - Harman, Claire (New York : Alfred A. Knopf, 2019)
"From the prize-winning biographer--the fascinating, little-known story of a Victorian-era murder that rocked literary London, leading Charles Dickens, William Thackeray, and Queen Victoria herself to wonder: can a novel kill? In May 1840, Lord William Russell, well known in London's highest social circles, was found with his throat cut. The brutal murder had the whole city talking. The police suspected Russell's valet, Courvoisier, but the evidence was weak. And the missing clue lay in the unlikeliest place: what Courvoisier had been reading. In the years just before the murder, new printing methods had made books cheap and abundant, the novel form was on the rise, and suddenly everyone was reading. The best-selling titles were the most sensational true-crime stories. Even Dickens and Thackeray, both at the beginning of their careers, fell under the spell of these tales--Dickens publicly admiring them, Thackeray rejecting them. One such phenomenon was William Harrison Ainsworth's Jack Sheppard, the story of an unrepentant criminal who escaped the gallows time and again. When Courvoisier finally confessed his guilt, he would cite this novel in his defense. Murder By the Book combines the thrilling true-crime story with a illuminating account of the rise of the novel form and the battle for its early soul between the most famous writers of the time. It is a superbly researched, vividly written, fascinating read from first to last"--
A last walk -- The crime -- This nightmare of a book -- The play -- The investigation -- The trial -- In the Stone Jug -- The execution -- The aftermath -- Postscript : unanswered questions.
"This is a Borzoi Book."
Includes bibliographical references (pages 217-244) and index.
Keywords: Courvoisier, Francois Benjamin, -- -1840 -- Trials, litigation, etc; Russell, William, -- Lord, -- 1767-1840.; Ainsworth, William Harrison, -- 1805-1882.; Murder -- England -- London; Murder in literature